Comparison of block characteristics of spinal anesthesia following intravenous dexmedetomidine and clonidine - Akansha Agrawal; Sanjay Agrawal; Yashwant S Payal (Wolters Kluwer Medknow Publications, 2016)
Background and Aims: Different routes of administration of α2 adrenergic receptor agonists have been found to prolong the duration of spinal block. Material and Methods: One hundred and twenty patients, aged 18-60 years, of ASA physical status I or II posted for elective fixation of fractures of lower limb under spinal anesthesia were selected. Spinal anesthesia was administered with 2.5 ml of 0.5% bupivacaine mixed with 10 μg fentanyl. The patients were randomized to receive intravenous (IV) dexmedetomidine 1 μg/kg/h for 15 min followed by infusion of 0.3 μg/kg/h (Group I), IV Clonidine 2 μg/kg/h for 15 min followed by infusion of 0.5 μg kg/h (Group II) or 15 ml of normal saline for 15 min followed by infusion at 50 ml/h (Group III). Motor and sensory blockade was evaluated using bromage score and pin prick method respectively. Results: The median block height in all groups was T8. Time to achieve block height was fastest in Group I. Time of regression of sensory block to T12/L1 dermatome was 230.75 ± 21.25 min (Group I), 196.25 ± 20.27 min (Group II) and 163.88 ± 15.46 min (Group III) respectively. Regression of motor blocks to Bromage 0/1 was 274 ± 21.25 min, 234.25 ± 32.41 min and 130.12 ± 20.70 min in Groups I, II and III respectively. Bradycardia was seen in one patient in Group I and two patients in Group II. Hypotension was seen in five patients in Group I and seven patients in Group II. First requirement for postoperative analgesic was after 353.13 ± 39.60 min, 314.38 ± 30.64 min and 193.25 ± 17.74 min in Groups I, II and III respectively. Conclusion: IV α2 agonists are useful adjuvants for prolongation of the duration of spinal block. IV dexmedetomidine produces a better clinical profile compared to clonidine.